Estimativas econométricas para as importaç\~oes agregadas com dados das contas nacionais trimestrais: 1996-2010 - Raphael Rocha Gouvêa; Bernardo Patta Schettini (Instituto de Pesquisa Econômica Aplicada (IPEA), 2011)
– This paper shows new econometric estimates for the Brazilian function of aggregate imports. Besides the basic relation, which includes income and relative price and identifies a demand equation (canonic model), we explore the pronounced co-movements between total imports, household consumption and gross fixed capital formation (alternative model). Using Quarterly National Accounts data is an innovation of the paper, as well as the investigation of parametric instability by different techniques - cointegration with structural breaks, markovswitching regressions, and Kalman filter estimations of varying parameters. There is evidence of nonlinearities in data generating processes for each series as well as in the imports equations. The evolution of imports is strongly related to income and the composition of the domestic absorption, being small the exchange rate impact. It should be noted that, in the out-ofsample assessment, the long-run vectors exhibited good performance only for the alternative model, while the error correction representations for the canonic model obtained the best results, possibly due to the different speeds of adjustment towards the long-run solution.
Keywords: F1; F17; C22; C52; 330